Drills for top-level hurdlers - Bedini, R. (New Studies in Athletics, 2012)
The 110m hurdler cannot run freely between the hurdles os in a sprinting race. He must correct the body posture, height of the hips above the ground and the length of each stride in accordance with the constraints on his running mechanism dictated by the effect of hurdle he has just cleared, by the proximity of next one he must clear and by fatigue in the later part of the race. This impacts running speed, particularly in the later part of the race, and the technique the athlete uses to adapt and maintain stride frequency is key to the final performance. The author, a scientist and successful coach, believes that many coaches over-emphasise the first half of the race, using workouts with only five to six hurdles, and do not prepare their athletes adequately to have the correct stride technique in the latter part of the race, where they are destined to decelerate. He suggests drills for maintaining stride frequency and improving foot push on the track without increasing stride length.